Halaman Redaktur - Vitae, Dewan Redaksi Educatio (Educatio Vitae, 2017)
Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae Halaman Redaktur Jurnal Educatio Vitae